Sosialisasi Demam Berdarah Dan Praktek Pembuatan Ovitrap Sederhana Di Kelurahan Bandarharjo Semarang - Aerrosa Murenda Mayadilanuari; Silvia Nurvita; Siti Noor Chotimah; Dody Indra Sumantiawan; Viny Natalia Dewi; Meita Fransiska Dara Antidi; Aldi Rizki Yudistira (Jurnal Kemitraan Masyarakat, 2024)
Dengue Hemorrhagic Fever (DHF) remains a serious health issue in Semarang City, particularly in Bandarharjo Sub-district. In an effort to address this problem, a community service activity titled "Socialization of Dengue Fever and Practice of Making Ovitrap in Bandarharjo Sub-district, Semarang" was conducted. The main objective of this activity is to increase public knowledge about the dangers of DHF and its prevention methods, with a focus on making simple ovitraps as one of the methods to control the population of Aedes aegypti mosquitoes. The event was attended by health cadres from RW. 6 in Bandarharjo Sub-district, with 27 participants actively participating. The topics covered included information about DHF, Aedes mosquitoes, the WINGKO program (Wolbachia in Semarang City), and the practice of making ovitraps. The outcome of this activity is expected to enhance public awareness of DHF, reduce DHF cases, and improve the community's ability to prevent DHF independently.